A Legal Review of Sailing Approval Letter: Systems and Procedures - Abbas Abbas; Syahruddin Nawi; Hamzah Baharuddin; Ilham Abas (Jambura Law Review, 2021)
Every ship that is going to sail is required to have a sailing approval letter issued by the harbormaster as an effort to control the security and safety of shipping. This research is a normative-legal research using a statute, comparative and conceptual approaches.The results show that the harbormaster as a government official at the port carries out and supervises efforts to fulfill shipping safety and security as a government administrative action by issuing a state document in the form of a sailing approval letter through a system of procedures for issuing a sailing approval letter. This letter is given to every ship that will sail or leave the port by ensuring that the ship, crew and cargo have technically-administratively fulfilled all sailworthiness requirements. The compliance of all parties in implementing the procedure for the issuance of the sailing approval will lead to the achievement of safety and security in shipping.